THYROID HORMONE LEVELS AS A PROGNOSTIC PREDICTOR FACTOR IN SEPSIS PATIENTS - Biya, Taufik R; Aman, Andi Makbul; Umar, Husaini; Sanusi, Himawan; Adam, Fabiola MS; Abadi, Satriawan; Siampa, Vindy Nugraha (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Sepsis is a systemic inflammatory response syndrome with high mortality. Early and accurate prediction of outcome in sepsis is important. In critically ill patients, there is significant disturbance of the Hypothalamic–Pituitary–Thyroid (HPT) axis. Changes in thyroid hormone in critical conditions such as sepsis are associated with high mortality. This condition is manifested by a normal or low decrease in serum free triiodothyronine (FT3), free thyroxine (FT4) and thyroid-stimulating hormone (TSH). Thyroid hormone levels can decrease significantly as sepsis progresses. Therefore, this study is important to describe the profile of thyroid function in septic patients. METHODOLOGY This was a cross-sectional, observational study conducted at RSUP Dr. Wahidin Sudirohusodo, Makassar, South Sulawesi. The study was conducted from January 2023 to May 2023. Patients diagnosed with sepsis were examined for thyroid hormone levels. The primary endpoint was the patient survival rate. The secondary end point was death during treatment. The statistical tests used were the Mann Whitney test and the Kruskall Wallis test. Statistical test results are considered significant if the p value